Henry James and the poetics of duplicity - Tredy, Dennis; Duperray, Annick; Harding, Adrian (Cambridge Scholars Publishing, 2013)
'Henry James and the Poetics of Duplicity' aims to advance the field of studies on the life and work of Henry James by fully exploring the author's use of duplicity, one of the key literary and rhetorical strategies within the author's vast andinfamous arsenal of techniques of 'ambiguity'. The collection brings together essays by both long established and more recent Jamesian scholars from 11 different countries, the collective work of whom, through this publication, further enhances our grasp of the ever-elusive literary style of Hnry James.